Addressing guideline and policy changes during pragmatic clinical trials. (August 2019) - Curtis, Lesley H; Dember, Laura M; Vazquez, Miguel A; Murray, David; DeBar, Lynn; Staman, Karen L; Septimus, Edward; Mor, Vincent; Volandes, Angelo; Wells, Barbara L; Huang, Susan S; Green, Beverly B; et al.
While conducting a set of large-scale multi-site pragmatic clinical trials involving high-impact public health issues such as end-stage renal disease, opioid use, and colorectal cancer, there were substantial changes to both policies and guidelines relevant to the trials. These external changes gave rise to unexpected challenges for the trials, including decisions regarding how to respond to new clinical practice guidelines, increased difficulty in implementing trial interventions, achieving separation between treatment groups, and differential responses across sites. In this article, we describe these challenges and the approaches used to address them. When deliberating appropriate action in the face of external changes during a pragmatic clinical trial, we recommend considering the well-being of the participants, clinical equipoise, and the strength and quality of the evidence associated with the change; involving those charged with data and safety monitoring; and where possible, planning for potential external changes as the trial is being designed. Any solution must balance the primary obligation to protect the well-being of participants with the secondary obligation to protect the integrity of the trial in order to gain meaningful answers to important public health questions.